2014
DOI: 10.1080/07907184.2013.874997
|View full text |Cite
|
Sign up to set email alerts
|

History, Structure and Action in the Settlement of Complex Conflicts: The Northern Ireland Case

Abstract: ABSTRACT. This article argues for a historical-structural approach to explaining conflict and settlement. It argues that the manner in which institutions function and actors pursue their ends is in part determined by slow-moving inter-linked structural relationships whose logic, trajectory and effects can only be identified historically. In complex conflicts such structural configurations generate tendencies to conflict and settlement requires that they be weak-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
0
7
0
2
Order By: Relevance
“…Political agreement was reached and sustained only with the Good Friday Agreement (GFA) of 1998. The research reported here began in 2003, five years after the GFA, as a long process of political and economic equalisation of the communities there was coming to completion (Ruane and Todd ). It was a period of economic boom in the South, and peace and slowly improving community relations in the North (Morrow et al.…”
Section: Comparison and Methodsmentioning
confidence: 99%
“…Political agreement was reached and sustained only with the Good Friday Agreement (GFA) of 1998. The research reported here began in 2003, five years after the GFA, as a long process of political and economic equalisation of the communities there was coming to completion (Ruane and Todd ). It was a period of economic boom in the South, and peace and slowly improving community relations in the North (Morrow et al.…”
Section: Comparison and Methodsmentioning
confidence: 99%
“…The overwhelming political presence of the UK was balanced by a strong diplomatic initiative in the USA which at once reduced US support for violent republicanism and brought in the US on the side of constitutional nationalism, with the EU brought into play as a model of shared sovereignty and a legitimator of Irish aims 6 . The resulting settlement was seen as a diplomatic triumph for a small state which gradually and through dialogue and persuasion shifted the direction of British state policy in Northern Ireland 7 . Irish elites saw no reason to change a diplomatic style which had worked so well.…”
Section: • the Vulnerability Of The Good Friday Agreementmentioning
confidence: 99%
“…But the lessons of the last thirty years of British-Irish negotiations are that innovative and mutually beneficial agreements can be developed by working within this complex and sensitive territory 29 .…”
Section: New Political Linkages and Modes Of Representationmentioning
confidence: 99%
“…L'armée britannique en Irlande du Nord: force d'interposition ou lutte anti-terroriste? 13 En Août 1969, Londres décida d'envoyer l'armée en renfort pour aider les forces de police locales à rétablir l'ordre. L'arrivée de l'Armée britannique en Irlande du Nord est perçue comme positive de la part de la minorité nord-irlandaise.…”
unclassified
“…Il est donc une étape cruciale dans l'évolution de la politique britannique en Irlande du Nord: pour la première fois, Londres choisissait de rompre avec le bloc unioniste et cessait de lui déléguer ou de partager avec lui l'administration de cette partie du territoire britannique. Alors que d'une certaine manière, comme on a pu le voir plus haut, l'échec de Sunningdale avait révélé et renforcé cette dépendance britannique à l'égard du bloc unioniste nordirlandais, l'Accord Anglo-Irlandais, lui, y mettait fin 33 . …”
unclassified